Смислові глибини художнього простору Леся Мартовича - Піхманець, Р. (Слово і Час, 2011)
Стаття присвячена з’ясуванню художніх параметрів концепту забобону у творчій свідомості Леся Мартовича. Простежено його природу, полісемантику й особливості вияву на різних рівнях тексту. The article deals with literary parameters of superstitions in Les Martovych’s poetic consciousness. The author explores the polysemantic nature of superstitions as well as their manifestations on different text levels.